The Prediction of Cracking Load and Peak Load of UHPC-NC Composite Structure - Yanru Chen; Wei Mao (Advances in Civil Engineering)
In this study, models for calculating the cracking load and a peak load of the UHPC-NC structures are established. The effects of UHPC's high tensile strength, reinforced steel bars in NC, reinforce steel bars in UHPC, and prestress tendons in UHPC on cracking load and peak load are considered. In the cracking load model, UHPC is considered to be elastic and the stress distribution is triangular, the stress of steel bars and prestressing tendons is also calculated according to the plane section assumption and elastic theory. In the peak load module, UHPC is assumed to be partially elastic and partially plastic. The plastic part is represented by a rectangular stress block diagram, and the stress value reduction factor and rectangular stress frame height reduction factor are obtained by trial calculation. Compared with the experimental data of UHPC-NC beams with different types of combinations collected from references, the calculated results have a high matching degree, which is suitable for various types of UHPC-NC, both cracking loads and peak loads.